2019
DOI: 10.7717/peerj.6099
|View full text |Cite
|
Sign up to set email alerts
|

Shifting faunal baselines through the Quaternary revealed by cave fossils of eastern Australia

Abstract: Fossils from caves in the Manning Karst Region, New South Wales, Australia have long been known, but until now have never been assessed for their palaeontological significance. Here, we report on late Quaternary faunal records from eight caves in the region. Extinct Pleistocene megafaunal taxa are recognised in two systems and include giant echidnas (Tachyglossidae gen. et sp. indet.), devils (Sarcophilus laniarius), koalas (Phascolarctos stirtoni), marsupial ‘lions’ (Thylacoleo carnifex), and kangaroos (Macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…It is possible that they were present but were decimated rapidly and never recorded in modern ecological surveys of the area. Similar extirpation records for small-bodied mammal species have been noted elsewhere in Australia (e.g., Fusco et al, 2016;Price et al, 2019).…”
Section: Diversitysupporting
confidence: 78%
“…It is possible that they were present but were decimated rapidly and never recorded in modern ecological surveys of the area. Similar extirpation records for small-bodied mammal species have been noted elsewhere in Australia (e.g., Fusco et al, 2016;Price et al, 2019).…”
Section: Diversitysupporting
confidence: 78%
“…For example, while eastern and western grey kangaroos (M. giganteus and M. fuliginosus, respectively) share an identical set of ZooMS peptide markers, the eastern species is today found in the eastern states of Australia, while the western species occurs in the southern and western parts of Australia [84]. However, the potential for recent local extinctions as well as range shifts should not be overlooked [19,[85][86][87]. Eastern and western kangaroo ranges overlap in south-central Australia, and a recent aDNA study has demonstrated that, historically, both species were found on Kangaroo Island, whereas it was previously thought that only the western variety had roamed there [88].…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%
“…Archaeologists, palaeontologists and other researchers have uncovered an assortment of faunal remains in Australia, dating from the late Pleistocene to the historical period [12][13][14][15][16][17][18][19]. However, the continent's often harsh environmental conditions [20][21][22], together with other factors like scavenging by marsupial carnivores [23][24][25], frequently result in a large number of highly fragmented, morphologically unidentifiable bone fragments in archaeological and palaeontological assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…A skeleton of an eastern grey kangaroo (M. giganteus) was recovered as a subfossil surface find in the Manning Karst Region of eastern New South Wales during part of a paleontological investigation (Price et al 2019). No animal was sacrificed or harmed in this study, and permissions to excavate were obtained from the landowner.…”
Section: Macropus Giganteus Skeletal Samplesmentioning
confidence: 99%